2010
DOI: 10.1002/pbc.22749
|View full text |Cite
|
Sign up to set email alerts
|

HOX gene expression in phenotypic and genotypic subgroups and low HOXA gene expression as an adverse prognostic factor in pediatric ALL

Abstract: HOX gene RNA expression cannot discriminate leukemia subgroups or relative maturity of leukemic cells. However, HOXA RNA expression correlates with prognosis, and particular HOX genes are expressed in specific genotypically characterized subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
(52 reference statements)
3
15
1
1
Order By: Relevance
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…This is fully compatible with the involvement of the HoxA family in stem cell expansion and leukemogenesis. [35][36][37][38] Using RNA interference-based functional screening, Cellot et al 39 identified the H3K4 demethylase JARID1B as a negative regulator of HSC functions among the Jumonji domain-containing family of histone demethylases. The shRNA-mediated knockdown of JARID1B leads to the in vitro expansion of HSCs, which is accompanied by the upregulation of HoxA7, HoxA9, and HoxA10, with preserved long-term reconstitution potential.…”
Section: Discussionmentioning
confidence: 99%
“…For the remaining groups, the prognosis is much worse, as indicated by 5‐year OS of 33% (±19%) in LYL1 ‐overexpressing group, 43% (±19%) in TAL1/LMO2 subtype and 30% (±24%) in TLX3 group. A recent study on HOXA overexpression demonstrated that it is related to an excellent prognosis with 6‐year relapse free survival (RFS) of 100% (patient HOXA expression above 75th percentile) (Starkova et al , 2010).…”
Section: Gene Expression Profilesmentioning
confidence: 99%
“…26,27 Thus, HIST1H2BD and HIST1H1E may be added to the growing list of acute leukemia-associated genes, for example DNMT3, EZH2, HOX family, and MLL, that 13 contribute to the leukemogenic process through deregulated CpG methylation or histone modification. [28][29][30][31] Among the other recurrent gene targets, most -CDKN2A, EBF1, ETV6, IKZF1, PAX5, RAG1, and TBL1XR1 -have been thoroughly discussed previously. 17,19,27,32,33 However, three of the presently identified gene targets, ADD3, ATP10A and PAN3, have been less emphasized in previous studies.…”
mentioning
confidence: 99%